ADAM17 Mediates Proteolytic Maturation of Voltage-Gated Calcium Channel Auxiliary α2δ Subunits, and Enables Calcium Current Enhancement. Issue 3 (17th March 2022) - Kadurin, Ivan; Dahimene, Shehrazade; Page, Karen M; Ellaway, Joseph I J; Chaggar, Kanchan; Troeberg, Linda; Nagase, Hideaki; Dolphin, Annette C
Abstract: The auxiliary α2 δ subunits of voltage-gated calcium (CaV ) channels are key to augmenting expression and function of CaV 1 and CaV 2 channels, and are also important drug targets in several therapeutic areas, including neuropathic pain. The α2 δ proteins are translated as preproteins encoding both α2 and δ, and post-translationally proteolyzed into α2 and δ subunits, which remain associated as a complex. In this study, we have identified ADAM17 as a key protease involved in proteolytic processing of pro-α2 δ-1 and α2 δ-3 subunits. We provide three lines of evidence: First, proteolytic cleavage is inhibited by chemical inhibitors of particular metalloproteases, including ADAM17. Second, proteolytic cleavage of both α2 δ-1 and α2 δ-3 is markedly reduced in cell lines by knockout of ADAM17 but not ADAM10 . Third, proteolytic cleavage is reduced by the N-terminal active domain of TIMP-3 (N-TIMP-3), which selectively inhibits ADAM17. We have found previously that proteolytic cleavage into mature α2 δ is essential for the enhancement of CaV function, and in agreement, knockout of ADAM17 inhibited the ability of α2 δ-1 to enhance both CaV 2.2 and CaV 1.2 calcium currents. Finally, our data also indicate that the main site of proteolytic cleavage of α2 δ-1 is the Golgi apparatus, although cleavage may also occur at the plasma membrane. Thus, our study identifies ADAM17 as a key protease required for proteolytic maturation of α2 δ-1 and α2 δ-3, and thus a potential drug target in neuropathic pain. Graphical Abstract: Abstract : The protease ADAM17 is important for proteolytic maturation of α2 δ-1, and calcium currents are reduced when expressed in ADAM17 knockout cells.